The Impact of Consumer Targeted Sales Promotion Programs on Their Trust in Brand – A field study in retail stores in KSA – - Alabdulkareem, Majed Abdulmohsen (Journal of Economic, Administrative and Legal Sciences, 2021)
This study aims to determine the effect of sales promotion programs directed to consumers on their confidence in the brand in retail stores operating in KSA as well as to investigate the statistical differences in the research variables according to some Demographics factors The study population consists of retail store customers in the city of Riyadh, and the Purposive Sample method was used in the study, which reached (390).The descriptive methodology is used and the questionnaire is the key tool to collect the primary data The study reached a set of important results, the most prominent of which were: it was found that there is a statistically significant positive effect of consumer attitudes towards sales promotion programs on brand Trust There is also a positive statistical correlation between them, reaching 53%.Discounts have been one of the most sales promotions A positive impact on trust in the brand, as it alone explained (20%) of the changes in trust in the brand and it was also found that there are statistically significant differences in consumer attitudes towards sales activation programs due to the difference in educational qualification Finally, the study recommendations, Reconsidering some activation programs that do not interact with the customer's trust towards the brand and attention to raising safety indicators in dealing with the brand due to its close association with the brand trust.
Keywords: promotion; marketing communication; marketing; sales; consumer behaviour